2005
DOI: 10.1542/peds.2005-1877
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Contraception

Abstract: Teen birth rates in the United States have declined during the last decade but remain much higher than rates in other developed countries. Reduction of unintended pregnancy during adolescence and the associated negative consequences of early pregnancy and early childbearing remain public health concerns. Emergency contraception has the potential to significantly reduce teen-pregnancy rates. This policy statement provides pediatricians with a review of emergency contraception, including a definition of emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…All knowledge items were based on the information outlined in the American Academy of Pediatrics EC policy statement. 5 Residents were also asked: “Have you ever attended a teaching session where EC was discussed?”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All knowledge items were based on the information outlined in the American Academy of Pediatrics EC policy statement. 5 Residents were also asked: “Have you ever attended a teaching session where EC was discussed?”…”
Section: Methodsmentioning
confidence: 99%
“…24 Adolescent access to EC is controlled exclusively by prescription in nearly all states. In spite of guidelines that urge providers to counsel all adolescents about EC and encourage advanced prescription, 5,6 previous research suggests that a majority of pediatricians in practice and training do not routinely counsel patients about EC and have not prescribed it. 7–9 …”
mentioning
confidence: 99%
“…Generally, many studies reported evidence that swimming ability is one of the prevention strategies that may beneficial and have some protective function against drowning (Brenner, 2003). Studies in Canada reported that most of drowning victims did not know how to swim nor had a weak swimming ability (The Canadian Red Cross Society, 2003).…”
Section: Swimming Abilitymentioning
confidence: 99%
“…It is generally accepted that emergency contraception is a safe and effective method of preventing pregnancy 1,2. Appropriate use of emergency contraception has the potential to prevent up to 75% of unplanned pregnancies3, yet approximately 3.5 million unintended pregnancies occur each year in the United States 4.…”
Section: Introductionmentioning
confidence: 99%